Repellent Power of Kuit Lime Peel Ethanol Extract (Citrus amblycarpa L.) Against Aedes aegypti Mosquitoes - Azzahra, Farah Nabila; Hastutiek, Poedji; Lazuardi, Mochamad; Suprihati, Endang; Kurnijasanti, Rochmah; Sunarso, Agus (Universitas Airlangga, 2025)
This research investigated the capability of the kuit lime peel ethanol extract as a repellent against Aedes aegypti mosquitoes. This study used the post test only control group design approach and the experimental method recommended by the World Health Organization Pesticides Evaluation Scheme (WHOPES) with modification. This study used seven different experiment groups consisting of a negative control group using a mixture of Tween 20 and aquadest, a positive control group using commercial mosquito repellent (Autan®), and concentration groups using 5%, 15%, 30%, 45%, and 60% (m/v) of the kuit lime peel ethanol extract. Each experiment groups were applied on a volunteer’s arms that are then inserted in a testing cage containing 25 female adult Ae. aegypti mosquitoes. Every mosquito that landed on the arm testing area will be calculated during the examination time (every 2 min for 30 min) to determine the repellent protection power percentage. Based on the result of the study using Two-Way Analysis of Variance and Duncan’s Multiple Range Test, the kuit lime peel ethanol extract is confirmed to be the most effective as a repellent against Ae. aegypti mosquitoes at the 30% concentration and until the 29th minute post-application with a 100% protection power.